A proposed model program to audit the contribution of municipal institutions to achieving the environmental dimension of sustainable development "applied research" (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract               The research aimed to prepare an audit program focusing on the activities of municipal institutions related to the environmental dimension as one of the dimensions of sustainable development, and applying the program for the purpose of preparing an oversight report related to assessing the impact of the activities of municipal institutions on the environmental reality as the main channel through which municipal institutions contribute to achieving the part related to it. Among the requirements of sustainable development, the proposed program was prepared and applied to the institutions affiliated to the Directorate of Municipalities of Karbala according to data over a time period starting from the year 2016  to 2020. To the effect that auditing the environmental dimension in municipal institutions contributes to achieving sustainable development, and the research procedures are represented by preparing a proposed auditing program and applying it in the municipal institutions, which are seven institutions, and preparing a report on the results of auditing the impact of the activities of municipal institutions on achieving the requirements of the environmental dimension of sustainable development, as the report diagnosed shortcomings And the imbalance in the municipal institutions related to the environmental aspect of sustainable development. The researcher reached conclusions, the most important of which are:•  Auditing the environmental dimension in municipal institutions leads to urging them, if they act according to the notes of the report, to address the obstacles to advancing their activities in accordance with the requirements of sustainable development.• The procedures followed in the treatment of waste in its various forms are characterized by a lack of observance of the necessary standards and precautions that ensure the reduction of pollution resulting from waste to the lowest possible extent in accordance with the requirements and goals of sustainable development.The researcher recommended the necessity of adopting the regulatory authorities, and in particular the Federal Bureau of Financial Supervision, the approach to auditing sustainable development in institutions, and introducing this approach as part of the annual audit plans approved by the Bureau.